Genetic features of Lynch syndrome in the Israeli population. (28th November 2014) - Goldberg, Y.; Barnes‐Kedar, I.; Lerer, I.; Halpern, N.; Plesser, M.; Hubert, A.; Kadouri, L.; Goldshmidt, H.; Solar, I.; Strul, H.; Rosner, G.; Baris, H.N.; et al.
<x xml:space="preserve">Abstract</x> Diagnosis of Lynch syndrome (LS) may be complex. Knowledge of mutation spectrum and founder mutations in specific populations facilitates the diagnostic process. Aim of the study is to describe genetic features of LS in the Israeli population and report novel and founder mutations. Patients were studied at high‐risk clinics. Diagnostics followed a multi‐step process, including tumor testing, gene analysis and testing for founder mutations. LS was defined by positive mutation testing. We diagnosed LS in 242 subjects from 113 families coming from different ethnicities. We identified 54 different mutations; 13 of them are novel. Sixty‐seven (59%) families had mutations in MSH2, 20 (18%) in MSH6, 19 (17%) in MLH1 and 7 (6%) in PMS2; 27% of the MSH2 mutations were large deletions. Seven founder mutations were detected in 61/113 (54%) families. Constitutional mismatch repair deficiency (CMMR‐D) was identified in five families. Gene distribution in the Israeli population is unique, with relatively high incidence of mutations in MSH2 and MSH6. The mutation spectrum is wide; however, 54% of cases are caused by one of seven founder mutations. CMMR‐D occurs in the context of founder mutations and consanguinity. These features should guide the diagnostic process, risk estimation, and genetic counseling.